Training of Moria choir conductor members and conductors in efforts to improve quality in Medan city - Deliana, Frida; Suprayitno (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
In ecclesiastical worship activities in the Christian community, singing activities both in the format of 'choir', congregational singing and others are integrated in a series of worship services in the church. It is also found among members of the Runggun Benameriah Protestant Karo Batak Church (GBKP) congregation who also use the choir format in activities to praise and glorify God. For Christians singing is a spiritual need. In both churches there are several types of choirs, both the choir moria (mothers), mamre choirs (fathers) gem choirs or youth / youth and elderly choirs. Each choir has a trainer (amateur) who also acts as choir leader, referred to as Dirigen. The problem is that often the quality of the choir that is displayed is low. This means that there are always a lot of technical errors and un-melodious voices from the choir members during the choir presentation. If this condition continues and occurs continuously, the presence of the choir can eventually interfere with the implementation of worship. Another condition is that almost all Dirigens in the GBKP choir are people who have limited musical abilities, and have no background in formal music education. His managerial ability and technical ability to teach choir is very weak. Dirigen's lack of musical knowledge and technical ability will certainly have a profound impact on the quality of the choir he leads. Therefore this dedication team will improve the choir management ability in vocal material and the ability of conducting to all participants so as to minimize the technical difficulties found in the preparation and presentation of the choir. This community service activity is expected that members and conductors / choir leaders can utilize their knowledge and experience as professionals in the field of choir training among community members in general.